Lignocellulose biorefinery engineering : principles and applications - Chen, Hongzhang (Cambridge, UK : Woodhead Publishing, 2015)
Biomass resources and their refining are key research topics internationally as alternatives to fossil fuel resources and oil refining. This book explores the heterogeneous nature of lignocellulosic biomass, which restricts its use as a raw material, and describes the theoretical basis of the lignocellulose refinery. It puts forward the theory of the integrated biomass refinery system, which produces multiple products, including biofuels, biomaterials, biochemicals, food and feed based on careful fractionation of the raw material. Chapter 1 introduces the significance and development of ligno.
2.6.1. Analysis methods for lignocellulosic materials2.6.2. Analysis methods for the biorefinery process; 2.6.3. Analysis methods for products; References; Chapter 3: Lignocellulose biorefinery feedstock engineering; 3.1. Overview; 3.2. Technologies of components fractionation; 3.2.1. Molecular level selective fractionation technology; 3.2.2. Cell-level selective fractionation technology; 3.2.3. Tissue-level selective fractionation technology; 3.3. Technologies of selective structure deconstruction; 3.3.1. Introduction to selective structure deconstruction technologies.
Includes index.
Includes bibliographical references at the end of each chapters and index.
Online resource; title from PDF title page (ScienceDirect, viewed March 11, 2015).
Elsevier
Keywords: Lignocellulose -- Biotechnology; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Biomass energy; Electric power production; Power resources; Lignocellulose -- Biotechnology; Electronic books; Electronic books